Comparison of SRIM, MCNPX and GEANT simulations with experimental data for thick Al absorbers - Evseev, Ivan G.; Schelin, Hugo R.; Paschuk, Sergei A.; Milhoretto, Edney; Setti, Joao A. P.; Yevseyeva, Olga; de Assis, Joaquim T.; Hormaza, Joel Mesa [UNESP]; Diaz, Katherin S.; Lopes, Ricardo T. (Pergamon-Elsevier B.V. Ltd, 2010)
Proton computerized tomography deals with relatively thick targets like the human head or trunk. In this case precise analytical calculation of the proton final energy is a rather complicated task, thus the Monte Carlo simulation stands out as a solution. We used the GEANT4.8.2 code to calculate the proton final energy spectra after passing a thick Al absorber and compared it with the same conditions of the experimental data. The ICRU49, Ziegler85 and Ziegler2000 models from the low energy extension pack were used. The results were also compared with the SRIM2008 and MCNPX2.4 simulations, and with solutions of the Boltzmann transport equation in the Fokker-Planck approximation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Proton beams; Nuclear tomography; Energy measurement; Monte Carlo methods